Association between Depression and Cognitive Impairment in Older Adults from a Comprehensive Care Center in Lima - Juliet Guillén; Carlos David Neyra Rivera; Fernando Runzer Colmenares; Ericson Gutiérrez (Universidad de las Ciencias Médicas de Cienfuegos, 2022)
Background: the mental and cognitive health of older adults can present changes related to aging. Depression often leads to cognitive impairment, conditions that must be identified for timely detection and prevention of damage. Objective: to determine the association between the level of depression and cognitive impairment in older adults from a comprehensive care center in the city of Lima, Perú. Methods: a cross-sectional and analytical study was carried out in adults over 60 years of age, attending a center for the elderly in Lima, between January and July 2017. Cognitive deterioration was considered the dependent variable and the independent variables were depression and characteristics. sociodemographic. Descriptive statistics were performed based on the calculation of frequencies, percentages, dispersion and measures of central tendency. To find the association between the independent variables and cognitive impairment, the Chi-square test or Fisher's exact test was used. The calculations were made with a confidence level of 95 %. Results: the average age was 67.4±7.4 years. 20.7 % presented depression and 31.0 % cognitive impairment. In the bivariate analysis, it was found that the age of 70 years or more (p<0.001; OR=23.0 I.C. [6.68-79.15]), the educational level not superior (p=0.015; OR=4, 63 95% CI [1.25-17.16] and depression (p=0.012; OR=3.82 95% CI [1.3-11.24]) were associated with cognitive impairment. that only age was associated with cognitive impairment (p<0.001; OR=24.93 CI95 % [6.04-97.74]). Conclusions: older age, low educational level and depression were associated with cognitive impairment, of these factors, only age 70 years or older was an independent factor associated with cognitive impairment.